O discurso publicitário ao serviço da construção da identidade no Estado Novo: o caso de Mundo Gráfico - Duarte, Isabel Margarida (2017)
Advertising discourse is both a reflection of the context in which it is produced and an agent of change upon it. In the present study, we analysed the advertisements in the magazine Mundo Gráfico with the purpose of identifying some aspects of the Portuguese identity of the regime Estado Novo, namely the national identity and the individual identity, of the Portuguese man and woman of that time. Simultaneously, it was our purpose to identify the discursive strategies involved in the construction of these identities, in particular strategies of an enunciative-pragmatic nature, such as the identification of the enunciative voices in dialogue in the advertisements. Still, we looked at ads as textual manifestations of a genre, briefly identifying some of their characteristics.